Prediction of Pharmacokinetic Parameters from Ethanolic Extract Mane Leaves (Vitex pinnata L.) in Geothermal Manifestation of Seulawah Agam Ie-Seu’um, Aceh - Maulydia, Nur Balqis; Khairan, Khairan; Noviandy, Teuku Rizky (Malacca Pharmaceutics, 2023)
The Mane plant (Vitex pinnata L.) is traditionally used as medicine in Aceh Province, Indonesia. This study aimed to predict the pharmacokinetic parameters of compounds in the ethanolic extract of Mane leaf (EEML), including the absorption, distribution, metabolism, excretion, and toxicity (ADMET), by in-silico approach. The method used was to analyze the compounds using a web-predictor server and molecular docking. Gas chromatography-mass spectrometry (GCMS) analysis of EEML showed the presence of active compounds, including phytol (60.93%), acorenol (8.56%), n-hexadecanoic acid (4.89%), trans-Z-alpha-bisabolene epoxide (2.7%) and cedrane (2.03%). Lipinski's rule of five states that all compounds had a deviation of less than 2. Pharmacokinetic parameters suggested that phytol was moderately absorbed in the gastrointestinal tract and had a toxicity level of 5 with lethal doses (LD50) >5000 mg/kg. Molecular docking results showed that phytol could be used against the targeted enzyme Staphylococcus aureus. In conclusion, our study suggests that the active compounds of EEML may have potential as a drug candidate.